Disitamab Vedotin (RC48) for HER2-positive advanced breast cancer: a case report and literature review - Li, Yang; Zhang, Jingjiao; Cai, Zhengang; Gao, Xue; Zhang, Lina; Lu, Zhi; Wang, Xiaojie; Yu, Peiyao; Li, Jia; Fang, Fengqi (Frontiers in Oncology, 2023)
Background/Aim: Human epidermal growth factor receptor 2 (HER2)-positive breast cancer is associated with a higher risk of metastasis and poorer overall survival (OS) due to HER2 gene overexpression/amplification. Although anti-HER2 targeted therapy has shown survival benefits in HER2-positive advanced breast cancer (ABC) patients, long-term treatment often leads to drug resistance, complicating further treatment options. RC48, an antibody-drug conjugate (ADC), combines the benefits of antibody targeting with the cytotoxic effects of a small molecule drug. Case report: We present a case involving a female patient with HER2-positive ABC who developed drug resistance and disease progression following multi-line anti-HER2 targeted therapy. In this instance, RC48 exhibited anti-tumor activity in an ABC patient resistant to HER2-targeted therapy. After eight treatment cycles with 120 mg of RC48, the tumor size decreased and stabilized. Conclusion: This case report underscores the potential clinical value of RC48 as a promising treatment alternative for patients resistant to HER2 targeted therapies.